Quantum chemistry simulation of the electronic properties in [Au(NH3)2]NO3 and [Au(NCH)2][AuCl4] extended unsupported complexes. Issue 7 (2nd May 2020) - Mendizabal, Fernando; Miranda-Rojas, Sebastián; Castro-Latorre, Pablo
ABSTRACT: The understanding of closed-shell interactions has become of tremendous relevance in the ever-growing field of supramolecular chemistry. Here, we present a theoretical study in which we characterised the intermolecular interactions between gold-based building blocks, namely ([Au(NH3 )2 ]NO3 )n ( n = 1, 2, 4, 8) and ([Au(NCH)2 ][AuCl4 ])n ( n = 1, 2). Due to the complex nature of these interactions, several methods were used such as the MP2, CCSD(T), PBE-D3, B3LYP-D3, and CAM-B3LYP-D3 (DFT-D3) levels. In all models were found closed-shell contacts among the gold atoms, interactions that resulted in being consistent with the presence of a high ionic contribution and a dispersion-type interaction. The absorption spectra of these models were calculated by the single excitation time-dependent-DFT (TD-DFT) method and CC2 levels, being the aurophilic interactions mainly responsible for the bands in both types of models. The theoretical models agree with the experimental results.